Cloning and function analysis of a Saussurea involucrata LEA4 gene - Kong, Hui; Xia, Wenwen; Hou, Mengjuan; Ruan, Nan; Li, Jin; Zhu, Jianbo (Frontiers in Plant Science, 2022)
Late embryogenesis abundant proteins (LEA) help adapt to adverse low-temperature environments. The Saussurea involucrate SiLEA4, which encodes a membrane protein, was significantly up-regulated in response to low temperature stress. Escherichia coli expressing SiLEA4 showed enhanced low-temperature tolerance, as evident from the significantly higher survival numbers and growth rates at low temperatures. Moreover, tomato strains expressing SiLEA4 had significantly greater freezing resistance, due to a significant increase in the antioxidase activities and proline content. Furthermore, they had higher yields due to higher water utilisation and photosynthetic efficiency under the same water and fertilizer conditions. Thus, expressing SiLEA4 has multiple advantages: (1) mitigating chilling injury, (2) increasing yields, and (3) water-saving, which also indicates the great potential of the SiLEA4 for breeding applications.